Investigation on some factors affecting crack formation in high resistance aluminum alloys (Fracture and Structural Integrity, 2017)
Aluminum alloys having good mechanical properties are Al-Zn- Mg alloys (7xxx) and Al-Cu-Li alloys (Weldalite®). These alloys may be subjected to stress corrosion cracking. In order to overcome this problem the Al 7050 alloy has been developed and it is widely used for aerospace applications. Despite that, some components made of this alloy cracked during the manufacturing process including machining and chemical anodization. In a previous work cracked Al 7050 components have been analyzed in order to identify possible causes of crack formation. In this work the susceptibility of this alloy to intergranular corrosion has been analysed and compared with that of other high resistance aluminum alloys.
Keywords: Aluminum alloys; Al 7050; Fracture; Intergranular corrosion